2009
DOI: 10.5194/angeo-27-1701-2009
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interplanetary magnetic field dependence of the field-aligned currents for both Northern and Southern Hemispheres

Abstract: Abstract. The configuration of the Earth's magnetosphere under various Interplanetary Magnetic Field (IMF) and solar wind conditions alters the global distribution of FieldAligned Currents (FACs) at the high latitude ionospheres. We use magnetic field data obtained from the Iridium constellation to extend recent studies that infer the dependence of the global FAC configuration on IMF direction and magnitude, hemisphere and season. New results are a reduced IMF B y influence on the FAC configuration for the win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
89
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(115 citation statements)
references
References 48 publications
21
89
3
Order By: Relevance
“…Overall, our Swarm FAC patterns are consistent with previous results which are based on different data sets (e.g., Weimer, 2001;Christiansen et al, 2002;Papitashvili et al, 2002;Wang et al, 2005Wang et al, , 2008bAnderson et al, 2008;Green et al, 2009;He et al, 2012). The main purpose of the presented FAC patterns is to provide the framework for interpreting the auroral Hall currents derived at the same time.…”
Section: Dependence Of Facs On Season and Imfsupporting
confidence: 78%
“…Overall, our Swarm FAC patterns are consistent with previous results which are based on different data sets (e.g., Weimer, 2001;Christiansen et al, 2002;Papitashvili et al, 2002;Wang et al, 2005Wang et al, , 2008bAnderson et al, 2008;Green et al, 2009;He et al, 2012). The main purpose of the presented FAC patterns is to provide the framework for interpreting the auroral Hall currents derived at the same time.…”
Section: Dependence Of Facs On Season and Imfsupporting
confidence: 78%
“…For example, the influence of the IMF B y , which governs the direction of high-latitude flows arising from magnetopause reconnection, on the configuration of the dayside Birkeland currents is consistent with previous studies conducted in the Northern Hemisphere. The effect of the sign of IMF B y on the Birkeland current topology is reversed in the Southern Hemisphere due to the anti-symmetry of the reconnection site with respect to the noon-midnight meridian (Green et al, 2009). For southward IMF, the Birkeland current distributions derived from Iridium data do not show significant currents poleward of 80 • MLAT, whereas some previous results show statistically significant NBZ-sense currents for all IMF orientations.…”
Section: Introductionmentioning
confidence: 68%
“…The Birkeland currents are affected primarily by the Pedersen conductance, P , and Green et al (2009) have shown that the current densities on the dayside are markedly reduced during the winter months when the conductance due to solar EUV is generally lower. The solar EUV influence on P can be expressed in terms of the solar zenith angle as (Rasmussen et al, 1988):…”
Section: Conductance Normalizationmentioning
confidence: 99%
“…Reasons for a change in the pattern of seasonal dependence for the CRB location and weakening of the summer-winter contrast after ∼ 2008 in our data are not clear. Our original thought was that the seasonal variations in the CRB location are due to a poleward shift of summer field-aligned currents (e.g., Green et al (2009) and references therein). But this effect would not explain our data for period 2 although we do not know if the FAC seasonal shifts are still in effect (recent FAC data have not been statistically investigated, to the best of our knowledge).…”
Section: Discussionmentioning
confidence: 99%